Emerging Nanotheranostics for 5-Fluorouracil in Cancer Therapy: A Systematic Review on Efficacy, Safety, and Diagnostic Capability - How, Chee Wun; Teoh, Siew Li; Loh, Jian Sheng; Tan, Stella Li Kar; Foo, Jhi Biau; Ng, Hui Suan; Wong, Stephenie Yoke Wei; Ong, Yong Sze (Frontiers in Pharmacology, 2022)
The conventional concept of using nanocarriers to deliver chemotherapeutic drugs has advanced to accommodate additional diagnostic capability. Nanotheranostic agents (NTA), combining both treatment and diagnostic tools, are an ideal example of engineering-health integration for cancer management. Owing to the diverse materials used to construct NTAs, their safety, effectiveness, and diagnostic accuracy could vary substantially. This systematic review consolidated current NTAs incorporating 5-fluorouracil and elucidated their toxicity, anticancer efficacy, and imaging capability. Medline and Embase databases were searched up to March 18, 2022. The search, selection, and extraction were performed by the preferred reporting items for systematic reviews and meta-analysis (PRISMA) guidelines to ensure completeness and reproducibility. Original research papers involving 5-fluorouracil in the preparation of nanoparticles which reported their efficacy, toxicity, and diagnostic capability in animal cancer models were recruited. The quality of included studies was assessed using the Collaborative Approach to Meta-Analysis and Review of Animal Data from Experimental Studies (CAMARADES) checklist. Nine studies were eligible for the systematic review. There was no significant toxicity reported based on animal weight and organ histology. Complete tumor remission was observed in several animal models using chemo-thermal ablation with NTAs, proving the enhancement of 5-fluorouracil efficacy. In terms of imaging performance, the time to achieve maximum tumor image intensity correlates with the presence of targeting ligand on NTAs. The NTAs, which are composed of tumor-targeting ligands, hold promises for further development. Based on the input of current NTA research on cancer, this review proposed a checklist of parameters to recommend researchers for their future NTA testing, especially in animal cancer studies. Systematic Review Registration: website, identifier registration number.